Distinct expression of cytokeratin, N-cadherin and CD133 in circulating tumor cells of metastatic breast cancer patients. (August 2014) - Bock, Carolin; Rack, Brigitte; Huober, Jens; Andergassen, Ulrich; Jeschke, Udo; Doisneau-Sixou, Sophie
ABSTRACT : Aim: Circulating tumor cells (CTCs) appear as potential candidates to predict the ability of breast tumors to metastasize. Moreover, epithelial–mesenchymal transition (EMT) and stem cell features are major mechanisms for metastasis.Patients & methods: Using a triple fluorescence technique, the expression of EMT (N-cadherin) and stem cell markers (CD133) was analyzed in CTCs detected via cytokeratin in blood samples from 26 metastatic breast cancer patients.Results: We detected CTCs in 100% of the patients (n = 831 CTCs). In total, 67% of the CTCs were N-cadherin and CD133 negative. Nonetheless, 87.8 and 57.6%, respectively, of the CTCs that expressed one marker coexpressed the other. Both double-negative and double-positive CTCs were present in more than 90% of the patients. Within the CTCs of each patient, we demonstrated striking heterogeneities of marker expressions, cell shapes, clusters and sizes.Conclusion: These data outline the importance of characterizing CTCs, especially through stem cell and EMT markers.